A Viability Study of Waterborne Platooning on the Lower Rhine - Colling, Alina; Hekkenberg, Robert; van Hassel, Edwin (European Journal of Transport and Infrastructure Research, 2021)
To achieve a modal shift towards waterborne transport and to deal with the shortage of crewmembers, a platooning concept called the “Vessel Train” is explored for the inland navigation sector. A Vessel Train consists of a lead and various follower vessels. The lead vessel is fully manned and takes over the navigational and situational awareness responsibilities for the follower vessels. This leading action benefits the followers through increasing the vessels’ productivity and enabling crew cost savings. This article investigates the viability of the concept for the lower Rhine region, by presenting a cost model that compares the Vessel Train conditions to the current sailing conditions. This model is used to assess a case study where lead vessels operate on a liner service between Antwerp and Duisburg. Economically viable cases for the concepts’ early-stage application and fully matured implementation are identified, and boundary conditions are presented. The viable conditions vary depending on the vessel type and the operating regime of the reference vessel. A fully matured VT implementation requires a minimum of 26 participants, whereas an early-stage implementation requires 40 participants. The early-stage implementation additionally includes a minimum distance of 200 km to be spent sailing in the VT and the distance sailed in the VT has to amount to a minimum of 50% of the entire trip.